PROTOTYPE LINE FOLLOWING AUTOMATIC GUIDED VEHICLE (AGV) FOR UNIT LOAD DISPATCH IN AN OFFICE ENVIRONMENT (FUDMA JOURNAL OF SCIENCES, 2023)
Within the office environment, file dispatch from one desk to other by clerical officers is common place in the world particularly in countries where technology has not been critically deployed. This unskilled monotonous task should not necessarily be undertaken with the potential natural intelligent human beings. Human beings are created with natural intelligence; they can be trained to use this intelligence to handle skilled tasks like building a robot for instance. Therefore, this paper presents the development of a prototype line following AGV for unit load dispatch in an office environment. Although line following navigation technique is the cheapest in terms of installation cost. Nevertheless, appropriate sensor positioning to achieve effective tracking of curvy path is still a predominate challenge. This paper equally addresses this issue. Thus, presents the analysis for the evaluation of the critical entry angle of the AGV based on the IR sensor position. The AGV successfully traverse a unit load through the test path proving the effectiveness of the proposed method. Therefore, the AGV can replace the need for a clerical officer transferring mails between two point within an office environment. Whereas, the present work only considers material transport between two points, in the future we will like to consider material transport between several points within the office environment. This will require path flexibility which is not achievable with line following, thus, we will incorporate path planning and path tracking controller
Keywords: AGV, Unit load, Material transport, line following, IR Sensor